Intuiting, Socializing and Playing Around: Women’s Stories of Informal Learning in the Information Technology Field - Shauna Butterwick; Kaela Jubas; Hong Zhu; Jen Liptrot (Adult Education Research Conference, 2006)
This report is based on a study of the informal and alternative approaches to learning of women who are working in the rapidly expanding and changing IT field. Using their intuition, borrowing and sharing expertise, and through trial and error, study participants describe essential forms of learning often unacknowledged by both workers and employers
Keywords: Gender; Lifelong learning; Work; Technology